If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + k = 27 Solving 19 + k = 27 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + k = 27 + -19 Combine like terms: 19 + -19 = 0 0 + k = 27 + -19 k = 27 + -19 Combine like terms: 27 + -19 = 8 k = 8 Simplifying k = 8
| -6d-7=-21 | | 12x=8x+20 | | 19+k=27 | | 9b-7=38 | | 3/5+4x=0.4 | | |3n-12|=6 | | 23=25+r | | 5x^2+3x=92 | | .15+4x=0.4 | | -99d+[34-6+5]=6 | | a+2=29 | | 6(4x-8)=18x | | 0=x^3+2x^2+x | | y=x^3+2x^2+x | | 5k-20=4-3k | | 21-15k=26 | | 11=-3+2x | | -16k+97=2k-83 | | 3.75=k(0.5) | | 8.4=m(1.2) | | 3n-20/2=11 | | 3n-20/2=20 | | 8.4=(1.2) | | f(3)=-3x+1 | | 4n/7+8=20 | | x+39=9 | | 0.5y=0.73 | | f(-2)=-3(-2)+4 | | -2-42=-44 | | 4(y+5)=7y-7 | | 21-6x=14 | | 3y-3.8=3y-1.8 |